Knowledge and self—adult learners’ conceptions of learning implications for teaching in higher education - Sean Courtney (Adult Education Research Conference, 1996)
Reforming teaching in higher education will mean in part, understanding more about the learning process as it occurs within and outside the existential domain of the classroom. This study seeks to contribute to that understanding by focusing on the meaning that students attach to the term learning. Over a five-year period graduate students at a large Midwestern university completed an open ended instrument, the Learning Questionnaire. Analysis of data yielded two major conceptions of learning. The conceptions and their implications for the teaching process will be explored in this presentation.